Prototype of Fan Radiator Control System Diesel Machine Using Max6675 Type Transmitter and Type-K Thermocouple Sensor Based On Arduino Uno - Asep Nurhuda; Bartolomius Harpad; Sunarto (Politeknik Pertanian Negeri Samarinda, 2020)
This study aims to produce a Control System that can operate the radiator fan based on the temperature or temperature of the cooling water, this control system is made as an optimization in order to support the dynamism of the operator's work. The prototype of the automatic radiator fan control system is expected to be able to provide time efficiency and work effectiveness for the operator. The method in this study uses the prototype method. In this research, data collection techniques used are field studies, observations and literature studies. Tool testing is carried out using comparative testing and function tests documented with the minutes of testing. The final results of this study are in the form of Prototype of the Diesel Engine Radiator Fan Control System based on temperature or temperature.